Archaeology in the Digital Era Papers from the 40th Annual Conference of Computer Applications and Quantitative Methods in Archaeology (CAA), Southampton, 26-29 March 2012 - Earl, Graeme ca. 20./21. Jh; Verhagen, Jacobus Wilhelmus Hermanus Philippus 1966- (Computer Applications and Quantitative Methods in Archaeology, 2014)
The Conference on Computer Applications and Quantitative Methods in Archaeology is the leading conference on digital archaeology, and this volume offers a comprehensive and up-to-date account of the state of the field today. It features a selection of the best papers presented at the fortieth annual conference in 2012 and explores a multitude of topics of interest to all those working in digital archaeology